THE EFFECT OF RETURN ON EQUITY AND GROWTH ASSETS ON PRICE BOOK VALUE WITH DEBT TO EQUITY AS INTERVENING VARIABLES IN SUB COMPANIES METAL SECTOR LISTED IN INDONESIA STOCK EXCHANGE - Afdillah, Soraya; Sari, Maya (International Proceeding of Law and Economic, 2020)
This study aims to determine the effect of Return on Equity, Change In Total Assets on Price Book Value with Debt To Equity as an intervening in metal sub-sector companies listed on the Indonesia Stock Exchange.This research is associative research with documentation data collection techniques, the population in this study amounted to 16 companies and the sample taken was 14 companies. The sampling technique used is the purposive sampling technique. The method of analysis used is path analysis. The results  showed that Return On Equity has a positive and significant effect  on Debt To Equity, Return On Equity has a positive and insignificant  effect on  Price Book Value, Growth Assets affects  positive and insignificant  to Debt To Equity, Growth Assets have a positive and insignificant effect   on Price Book Value, Debt to Equity has a positive and insignificant  effect  on Price Book Value, Debt to Equity  as mediation on Return On Equity and Price Book Value  negatively and  insignificantly affecting, Debt to Equity as mediation on Growth Assets and Price Book Value negatively affecting   and insignificant.